Utilization of plasticine as a learning medium for students at State Elementary School 014 Munsalo Kopah - Irfandi Irfandi; Lasmiadi Lasmiadi; Andiyan Putra Widadi; Fil Ardi; Igo Prasenta; Muhammad Iqbal; Dila Puspita Sari; Mainur Sulvia; Mitra Aprideni; Alwitri Zulhijrani; Esiska Yulita; Delita Murni; Cahyani Agista; Dian Jusandi (Journal of Community Service in Science and Engineering (JoCSE), 2024)
The quality of learning is not only seen from the results obtained by students but also from the learning process. Quality learning is innovative learning using various learning media. Good learning media will make it easier for students to receive the material provided by the teacher. Community service at SDN 014 Munsalo Kopah village is carried out to provide innovation and variation in teachers' use of learning media in the learning process. Participants in this activity consist of students and teachers. The stages of implementing this activity consist of material presentations, discussions, demonstrations, and training. The results obtained from this service activity are increased student motivation and creativity in learning through plasticine learning media. Kualitas pembelajaran tidak hanya dilihat dari hasil yang diperoleh oleh peserta didik saja tetapi juga dari proses pembelajaran. Pembelajaran yang berkualitas adalah pembelajaran yang inovatif dengan menggunakan berbagai media pembelajaran. Media pembelajaran yang baik akan mempermudah peserta didik menerima materi yang diberikan guru. Pengabdian kepada masyarakat di SDN 014 desa munsalo kopah dilakukan untuk memberikan inovasi dan variasi penggunaan media pembelajaran oleh guru dalam proses pembelajaran. Peserta kegiatan ini terdiri dari peserta didik dan guru. Tahapan pelaksanaan kegiatan ini terdiri dari presentasi materi, diskusi, demontrasi dan pelatihan. Hasil yang di dapat pada kegiatan pengabdian tersebut adalah peningkatan motivasi dan kreativitas siswa dalam belajar melalui media pembelajaran plastisin.